Lorsque le blé de l'UE recule, les USA occupent le marché - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
La sécheresse intervenue en Europe a affecté les exportations de...